Theft of Digital Painting Artworks: A Review of the Legal Protection of Art Industry Perpetrators in Indonesia - Andila, Silvina; Silviana, Ana (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
As a result of globalization and technology breakthroughs, digital painting has become more popular in Indonesia and has enabled artists to display their work online. Still, art theft is a serious problem, especially for artists who contribute to the art industry.The purpose of this research is to find out the technological developments, impact, and legal protection against theft of digital painting cases against perpetrators of the art industry in Indonesia. Research methods are qualitative research with descriptive and analytical approaches. The conclusion of this study is that the dynamics of the art industry in Indonesia are heavily influenced by technological advances and the style of digital painting. The impact of the theft of digital painting works of art on perpetrators of the art industry in Indonesia is loss of recognition, financial losses, and violations of the law. The Legal protection to deal with theft of digital painting artworks against perpetrators of the art industry in Indonesia can be done in a variety of ways namely by registering Copyright by submitting an application for copyright registration, protection of Digital Painting, updating of legislative regulations leading to more detailed explanations relating to the artwork of Digital painting, and Legal awareness and education.